2017
DOI: 10.3390/fermentation3030040
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Engineering of Yarrowia lipolytica as a Promising Cell Biorefinery Platform for the de novo Production of Multi-Purpose Long Chain Dicarboxylic Acids

Abstract: This proof-of-concept study establishes Yarrowia lipolytica (Y. lipolytica) as a whole cell factory for the de novo production of long chain dicarboxylic acid (LCDCA-16 and 18) using glycerol as the sole source of carbon. Modification of the fatty acid metabolism pathway enabled creating a pool of fatty acids in a β-oxidation deficient strain. We then selectively upregulated the native fatty acid ω-oxidation pathway for the enhanced terminal oxidation of the endogenous fatty acid precursors. Nitrogen-limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 125 publications
(118 reference statements)
0
11
0
Order By: Relevance
“…The current price of biodiesel-derived glycerol varied from US $0.06 to US $0.11 per pound [15]. On the basis of microorganisms grown on biodiesel-derived waste glycerol, researchers developed the method of production of 1,3-propanediol [16], biomass-enriched lipids [17][18][19][20][21], carbonic acids (in particular, pyruvic acid [22]), α-ketoglutaric acid [23,24], citric acid [16,25,26], and butanol [27]. However, few reports showed the satisfactory growth of fungi of the genera Mucor, Cunninghamella, Thamnidium, Zygorhynchus, and Mortierella, and similarly for lipid synthesis when cultivated on glycerol [15][16][17][18][19]21,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The current price of biodiesel-derived glycerol varied from US $0.06 to US $0.11 per pound [15]. On the basis of microorganisms grown on biodiesel-derived waste glycerol, researchers developed the method of production of 1,3-propanediol [16], biomass-enriched lipids [17][18][19][20][21], carbonic acids (in particular, pyruvic acid [22]), α-ketoglutaric acid [23,24], citric acid [16,25,26], and butanol [27]. However, few reports showed the satisfactory growth of fungi of the genera Mucor, Cunninghamella, Thamnidium, Zygorhynchus, and Mortierella, and similarly for lipid synthesis when cultivated on glycerol [15][16][17][18][19]21,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Although the produced fatty acids were mainly accumulated in the cells without being secreted, there was no growth defect observed. Aligned with our work for metabolic engineering of Y. lipolytica to produce long-chain dicarboxylic acid (Abghari et al, 2017) and fatty alcohol (Wang et al, 2016), the current study further improved Y. lipolytica for production of long-chain (C16-C18) fatty acids.…”
Section: Discussionmentioning
confidence: 62%
“…DCA can be synthesized in Y. lipolytica from hydrophobic substrate such n-alkane and fatty acids and are usually the products of bioconversion. Moreover, production of DCA from de novo synthesis has been recently described for the production of long chain dicarboxylic acid (LCDCA-16 and 18) using glycerol as the sole source of carbon [ 50 ] allowing the production of 0.3 g/L LCDCA in shake flask. In our study, we showed that the strain ∆pox FAS-I 1220 W eg DGAT can produce up to 0.47 ± 0.07 g/L MCDCA in shake flask which give to the strain a great potential and represents the first example to our knowledge of de novo synthesis of DCA with length from 10 to 14 carbons.…”
Section: Discussionmentioning
confidence: 99%